Assessment of the Level of Knowledge and Management Practices of Preeclampsia among Pregnant Women in Southwest Nigeria - Mary Mojisola Obadimeji; Titilayo Olaoye; Chikwendu Amaike; Roland I. Funwei; Alexandra Onyeunoneme Odiari (Adventist University of Africa, 2023)
Background: Preeclampsia (PE) is a critical condition that poses a significant risk of maternal and fetal mortality, particularly in underdeveloped countries with limited access to health care. In such countries, the incidence of preeclampsia during pregnancy is estimated to be 10%. This study aimed to assess the understanding and management of PE care in pregnant women in Southwest Nigeria. Despite its high prevalence, there is a lack of information regarding the best management strategies for preeclampsia in the study location. Methods: A descriptive cross-sectional design was employed, and 331 individuals were recruited from 2,283 expectant mothers in the East Senatorial District of Osun State through a multi-stage selection process. Results: The participants demonstrated an average knowledge score of 10.2 out of 5.0, and 47.7% had a working knowledge of preeclampsia. However, less than half of the participants (46.2%) had completed secondary school. Conclusion: Based on these findings, it can be concluded that expectant mothers generally possess a reasonable level of knowledge regarding preeclampsia. However, this study emphasizes the importance of enhancing women's knowledge of preeclampsia through various means such as health education in maternity hospitals, media outlets, and national education programs.